Penanganan Covid-19 Dan Pengembangan Hukum Ham Konteks Indonesia - Faiq Tobroni (Institut Agama Islam Negeri Metro, 2020)
In dealing with the Covid-19 pandemic, the Indonesian government uses Large-Scale Social Restrictions (PSBB) as an option to accelerate the handling of Covid-19. There is a narrative struggle regarding the limitation of human rights behind the policy of implementing the PSBB. The research uses a form of normative juridical legal research. Retrieving data through documentation, and data analysis through reduction, data presentation and conclusion. The narrative struggle that occurs regarding the protection of rights in handling Covid-19 is shown by the tug-of-war between the interests of health and the rights of community activities, where the policy of limitation has implications for the fulfillment of life's needs. The implementation of PSBB in Indonesia must be done optimally by improving domestic human rights legal instruments by incorporating public health and safety factors as the legality of human rights restrictions.